Expressions of adenosine A2A receptors in coronary arteries and peripheral blood mononuclear cells are correlated in coronary artery disease patients. (1st March 2017) - Gariboldi, Vlad; Vairo, Donato; Guieu, Régis; Marlingue, Marion; Ravis, Eléonore; Lagier, David; Mari, Alissa; Thery, Elsa; Collart, Frédéric; Gaudry, Marine; Bonello, Laurent; Paganelli, Franck; et al.
Abstract: Background: Altered coronary blood flow occurs in patients with coronary artery disease (CAD). Adenosine strongly impacts blood flow mostly via adenosine A2A receptor (A2A R) expressed in coronary tissues. As part of a systemic regulation of the adenosinergic system, we compared A2A R expression in situ, and on peripheral blood mononuclear cells (PBMC) in CAD patients. Methods and results: Aortic and coronary tissues, and PBMC were sampled in 20 CAD patients undergoing coronary artery bypass surgery and consecutively included. Controls were PBMC obtained from 15 healthy subjects. Expression and activity of A2A R were studied by Western blotting and cAMP measurement, respectively. A2A R expression on PBMC was lower in patients than in controls (0.83 ± 0.31 vs 1.2 ± 0.35 arbitrary units; p < 0.01), and correlated with A2A R expression in coronary and aortic tissues (Pearson's r: 0.77 and 0.59, p < 0.01, respectively). Basal and maximal cAMP productions following agonist stimulation of PBMC were significantly lower in patients than in controls (120 ± 42 vs 191 ± 65 and 360 ± 113 vs 560 ± 215 pg/10 6 cells, p < 0.05, respectively). In CAD patients, the increase from basal to maximal cAMP production in PBMC and aortic tissues was similar (+ 300% and + 246%, respectively). Conclusion: Expression of A2A R on PBMC correlated with those measured in coronary artery and aortic tissues in CAD patients, A2A R activity of PBMC matched that observed in aorta, and A2A R expression and activity in PBMC were found reduced as compared to controls. Measuring the expression level of A2A R on PBMC represents a good tool to address in situ expression in coronary tissues of CAD patients.